Respiratory chemoreceptor function in vertebrates - Comparative and evolutionary aspects - Sundin, Lena; Burleson, Mark L.; Sanchez, Adriana P.; Amin-Naves, Jalile; Kinkead, Richard; Gargaglioni, Luciane H. [UNESP]; Hartzler, Lynn K.; Wiemann, Martin; Kumar, Prem; Glass, Mogens L. (Oxford University Press (OUP), 2007)
The sensing of blood gas tensions and/or pH is an evolutionarily conserved, homeostatic mechanism, observable in almost all species studied from invertebrates to man. In vertebrates, a shift from the peripheral O2-oriented sensing in fish, to the central CO2/pH sensing in most tetrapods reflects the specific behavioral requirements of these two groups whereby, in teleost fish, a highly O2-oriented control of breathing matches the ever-changing and low oxygen levels in water, whilst the transition to air-breathing increased the importance of acid-base regulation and O2-related drive, although retained, became relatively less important. The South American lungfish and tetrapods are probably sister groups, a conclusion backed up by many similar features of respiratory control. For example, the relative roles of peripheral and central chemoreceptors are present both in the lungfish and in land vertebrates. In both groups, the central CO2/pH receptors dominate the ventilatory response to hypercarbia (60-80), while the peripheral CO2/pH receptors account for 20-30. Some basic components of respiratory control have changed little during evolution. This review presents studies that reflect the current trends in the field of chemoreceptor function, and several laboratories are involved. An exhaustive review on the previous literature, however, is beyond the intended scope of the article. Rather, we present examples of current trends in respiratory function in vertebrates, ranging from fish to humans, and focus on both O2 sensing and CO2 sensing. As well, we consider the impact of chronic levels of hypoxia - a physiological condition in fish and in land vertebrates resident at high elevations or suffering from one of the many cardiorespiratory disease states that predispose an animal to impaired ventilation or cardiac output. This provides a basis for a comparative physiology that is informative about the evolution of respiratory functions in vertebrates and about human disease. Currently, most detail is known for mammals, for which molecular biology and respiratory physiology have combined in the discovery of the mechanisms underlying the responses of respiratory chemoreceptors. Our review includes new data on nonmammalian vertebrates, which stresses that some chemoreceptor sites are of ancient origin.
Keywords: Animalia; Invertebrata; Lepidosirenidae; Mammalia; Teleostei; Tetrapoda; Vertebrata